Regional economic cooperation in South Asia : Nepalese perspective - Banskota, N. P. (Delhi, 1990)
The book examines the progress made by SAARC in social, political and eco nomic fields, the structure of the compo sition and direction of South Asian trade, the export of manufactured goods, problems and prospects of the customs union and obstacles to regional -co-operation. In addition, it brings re cent bilateral issues of trade and transit between Indian and Nepal into a sharp focus.
Keywords: International economic relations